2020
DOI: 10.1002/anie.202009335
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular C(sp3)–H Bond Oxygenation by Transition‐Metal Acylnitrenoids

Abstract: This study demonstrates for the first time that easily accessible transition-metal acylnitrenoids can be used for controlled direct C(sp 3)-H oxygenations. Specifically, a ruthenium catalyst activates N-benzoyloxycarbamates as nitrene precursors towards regioselective intramolecular C À H oxygenations to provide cyclic carbonates, hydroxylated carbamates, or 1,2-diols. The method can be applied to the chemoselective CÀH oxygenation of benzylic, allylic, and propargylic C(sp 3)ÀH bonds. The reaction can be perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 57 publications
2
51
1
Order By: Relevance
“…To evaluate the catalytic activity of the premised Cp*M­(LX)Cl complexes, group 9 metal precursors (Co, Rh, and Ir) and hydroxyquinoline derivatives ( L1 and L2 ) were simultaneously screened. On the other hand, as the nitrene precursors, we chose azidoformate ( 1a ), , N- benzoyloxycarbamate (1b ), and N -tosyloxycarbamate ( 1c ), which were fruitfully utilized for the catalytic C–H amination reactions to give 2-oxazolidinone 2 as a common product.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the catalytic activity of the premised Cp*M­(LX)Cl complexes, group 9 metal precursors (Co, Rh, and Ir) and hydroxyquinoline derivatives ( L1 and L2 ) were simultaneously screened. On the other hand, as the nitrene precursors, we chose azidoformate ( 1a ), , N- benzoyloxycarbamate (1b ), and N -tosyloxycarbamate ( 1c ), which were fruitfully utilized for the catalytic C–H amination reactions to give 2-oxazolidinone 2 as a common product.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrene chemistry is traditionally used to incorporate nitrogen into a target molecule, either by nitrene addition to alkenes or by C−H amination [9] . In a recent surprising discovery, we found that nitrene chemistry can also be used as a tool to accomplish C(sp 3 )−H oxygenations (Figure 1b, upper reaction) [10] . The one‐step conversion of readily available alcohols to their corresponding N ‐benzoyloxycarbamates was followed by a ruthenium catalyzed formation of cyclic carbonates via the proposed intermediate formation of ruthenium nitrene species.…”
Section: Figurementioning
confidence: 94%
“…[9] In a recent surprising discovery, we found that nitrene chemistry can also be used as a tool to accomplish C(sp 3 )À H oxygenations (Figure 1b, upper reaction). [10] The one-step conversion of readily available alcohols to their corresponding N-benzoyloxycarbamates was followed by a ruthenium catalyzed formation of cyclic carbonates via the proposed intermediate formation of ruthenium nitrene species. However, unfortunately, this nitrene-mediated CÀ H oxygenation displayed critical drawbacks.…”
mentioning
confidence: 99%
“…Recently, Meggers and co-workers extended the use of this type of N-(2-pyridyl)NHC-derived ruthenium catalysts to C(sp 3 )-H activation of carbamates (Scheme 16). 46 Through a simple change in the substituents of the catalyst, they were able to attain C-N and C-O bond formation via nitrene and carbene insertions respectively. Since there was extensive literature precedent for ruthenium-catalysed nitrene insertions of carbamates, the authors focused instead on developing the C(sp 3 )-H oxygenation reaction to obtain cyclic carbonates.…”
Section: Chiral-at-ruthenium Catalysismentioning
confidence: 99%